Implementasi IoT dan Sensor Termal untuk Mitigasi Kebakaran Hutan dan Lahan dengan Penentuan Koordinat - Br Ginting, Nurul Devani; Handayani, Ade Silvia; Sarjana, Sarjana (Building of Informatics, Technology and Science (BITS), 2024)
Forest fires are a serious environmental problem, causing ecosystem damage, air pollution and economic losses. Effective monitoring and mitigation of forest fires requires early detection and tracking of hotspots that have the potential to become fire centers. This research proposes the implementation of Internet of Things(IoT) technology and thermal sensors to detect forest fires through point coordinate mapping using the triangulation method. The method used involves the installation of thermal sensors and NEO-6 GPS modules. The thermal sensor measures the ambient temperature in real-time, while the GPS module provides precise coordinate data in (latitude and longitude). Data from the sensors is transmitted to the ThingSpeak platform via the IoT network, where further analysis is performed to identify hot spots. A triangulation method is then applied to map the position of the hot spot. This research aims to develop a forest fire monitoring system capable of detecting and mapping hotspots in real-time, thus enabling quick and effective mitigation actions. The results obtained from this research show that the system can determine the position of hotspots with coordinate accuracy (latitude and longitude) within a margin of error of less than 5 meters.